Clinical Outcome and Prognostic Factors of Surgically Treated Acute Epidural Hematoma, A 32-Month Prospective Observational Study - Kebede, Biruk Mulugeta; Getachew, Kaleab; Bezu, Maihder Tewodros; Abebe, Mersha; Laeke, Tsegazeab (WFNS Journal, 2025)
Traumatic brain injury (TBI) is a leading cause of death and disability in young individuals, with acute epidural hematoma (AEDH) being a critical neurosurgical emergency. Advances in CT imaging and surgical techniques have reduced mortality from 86 to 5 to 12%.To assess the socio-demographic characteristics, clinical outcomes, and factors influencing prognosis in patients surgically treated for traumatic AEDH.A prospective cross-sectional study was conducted on 132 patients treated for AEDH between February 2020 and September 2022 at Tikur Anbessa Specialized Hospital and ALERT Trauma Center. Data were collected through interviews, chart reviews, and CT scans, and analyzed using SPSS version 25.Of the 132 patients, 92.4% were male, with a mean age of 30.8 years. Assault (59.1%) and road traffic accidents (25.8%) were the leading causes. Most hematomas (98.5%) were supratentorial and unilateral (91.6%), with the parietal region most commonly affected (61.4%). Preoperative Glasgow Coma Scale (GCS) scores of 14 to 15 were observed in 48.5% of cases, and 89.75% of patients had normal pupillary reactions. The mortality rate was 3%, with 6.8% discharged in a vegetative state and 75% achieving good recovery (GODS: 7–8). Poor outcomes were significantly associated with low postresuscitation GCS (p = 0.004), effacement of basal cisterns (p = 0.043), hemiparesis (p < 0.001), low oxygen saturation (p = 0.007), and abnormal pupillary reactions (p = 0.014).This study reports a low mortality rate in AEDH patients. However, key prognostic factors such as low GCS and pupillary abnormalities stress the need for rapid diagnosis and intervention to optimize outcomes.
Keywords: acute epidural hematoma; basal cistern; pupillary reaction; hemiparesis